THE FACTORS INFLUENCING CONSUMER PURCHASE DECISION IN CHOOSING TABLET PRODUCTS OF IBA STUDENTS - Korompis, Caecilia Eva Martina; Saerang, David Paul Elia; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2014)
Youth in this modern era, related with their intention to get information access quickly. Nowadays, there is a popular gadget that used by many people which called tablet. Tablet is a combination of cell phones and laptop. The students of IBA program as the youth who are studying, they need to have gadget which not only can be used to access the internet or social media, but also can help them in college activity. The objective of this research is to know what factors that influencing consumer purchase decision of IBA students in choosing tablet. The population observed is IBA students who have tablet with sample as many as 100 respondents. This research used quantitative method where this research spread questionnaire to obtain the primary data. Factor Analysis Method was used to analyzed the twenty variables of this research. The result and conclusions are from the twenty variables, seventeen variables formed five factors that influence consumer to purchase tablet products. Those factors are product, dependency, brand, usage and quality. There are three variables that do not significantly influence consumer to buy tablet products, namely: trend, curiosity, and friends. Besides those variables, there are also some additional factors that influence consumer in buying tablet products, which are: software application, accessories, feature, extra function, and product released year. The company that produces tablet products should pay attention to all the factors because it has significant influence to consumer purchase decision. Keywords: tablet products, consumer purchase decision.